2016
DOI: 10.1155/2016/3743420
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Therapy in Differentiated Thyroid Cancer

Abstract: Objectives. Invasion of differentiated thyroid cancer (DTC) into surrounding structures can lead to morbid procedures such as laryngectomy and tracheal resection. In these patients, there is a potential role for neoadjuvant therapy. Methods. We identified three studies involving the treatment of DTC with neoadjuvant chemotherapy: two from Slovenia and one from Japan. Results. These studies demonstrate that in selected situations, neoadjuvant chemotherapy can have a good response and allow for a more complete s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Indication of induction chemotherapy in inoperable DTC is not well established (9). Retrospective nonrandomized studies reported the benefit of cytotoxic agents in locally invasive follicular and papillary carcinomas prior to surgery (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Indication of induction chemotherapy in inoperable DTC is not well established (9). Retrospective nonrandomized studies reported the benefit of cytotoxic agents in locally invasive follicular and papillary carcinomas prior to surgery (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Other opportunities for redifferentiation of follicular cells and re- There are no studies with adjuvant TKI use in DTC, and very few with neoadjuvant chemotherapy. 64 As we begin to understand more about rapid tumour inhibition, this may become an option in selected populations when emerging data become available.…”
Section: Future Directionsmentioning
confidence: 99%
“…The results showed comparable response rates with a decrease in tumor size in both FTC and PTC (45% and 44% respectively) [9,10]. Dang et al, reviewed the effects of neoadjuvant chemotherapy in reducing morbid or complicated surgical resection [11]. Despite a few trials which showed beneficial results in locally invasive disease, the data had several limitations and neoadjuvant chemotherapy is not currently recommended [11].…”
Section: Introductionmentioning
confidence: 99%